Winter site use by Afro-Palearctic migrants in Ghana: site persistence and densities of Willow Warbler, Pied Flycatcher, Melodious Warbler and Common Redstart. (4th May 2019) - Thorup, Kasper; Sørensen, Iben Hove; Willemoes, Mikkel; Lerche-Jørgensen, Mathilde; Fjeldså, Jon; Tøttrup, Anders P; Jacobsen, Erik Mandrup; Reeve, Andrew H; Oteng-Appau, Robert; Asamoah, Augustus; Lehmberg, Thomas
Abstract : Little is known about the variation within and among species of long-distance migrants in behavioural strategies and habitat choice on their non-breeding grounds. We report results from regular ringing operations carried out during the winter seasons 2009–2013 and transect counts in 2013, 2015 and 2016 in the Sudan Savanna Zone in Ghana. The best supported capture–mark–recapture model included species-specific probabilities of stay between within-season periods but no differences in resighting probability among species or sites. This model indicated that less than one-third of the Willow Warblers Phylloscopus trochilus and half of the Melodious Warblers Hippolais polyglotta stayed at wintering sites during more than 10 d, whereas for Pied Flycatcher Ficedula hypoleuca and Common Redstart Phoenicurus phoenicurus up to 90% stayed for more than 10 d, indicating itinerant wintering behaviour in the warblers and longer non-breeding residency in Pied Flycatcher and Common Redstart. Densities varied among years, but Pied Flycatchers were consistently most numerous in well-matured woodland habitat and Willow Warblers in disturbed habitat. Recaptures among years were too low for meaningful estimates of winter site fidelity, yet recurrence was recorded in three species. We speculate that habitat use is directly related to degree of territory defence and itinerancy.